STUDENTS' PERCEPTIONS ON CHALLENGES OF THE USE OF ZOOM AND WHATSAPP AS SYNCHRONOUS AND ASYNCHRONOUS ONLINE LEARNING PLATFORMS IN SENIOR HIGH SCHOOL - Putri, Natasya Adelia (RETAIN : Journal of Research in English Language Teaching, 2023)
The COVID-19 pandemic made educational institutions apply online learning. A combination of two models of online learning is used, combining both synchronous and asynchronous learning. Zoom and WhatsApp are the popular online learning platforms to use in the teaching-learning process. This study aimed to investigate the perception of students towards the challenges of using Zoom and WhatsApp as the online learning platforms in order to support the online English teaching-learning process. A descriptive qualitative method was done and 32 senior high school students from SMA Dharma Wanita Surabaya participated. Open-ended and close-ended questionnaires were chosen as data collection methods, and the data were examined using flow model Miles and Huberman. The study reveals that using Zoom and WhatsApp as online learning platforms helped students in practicing English during the pandemic era, made teaching-learning process more effective and interactive, and facilitated interaction and communication between teacher and students. In addition, the features provided by Zoom and WhatsApp are very helpful and useful for students in learning English, especially in emphasizing reading skills. Even so, the use of Zoom and WhatsApp are challenging for students because of unreliable internet connection, limited internet quota, storage and space availability and unsupported digital devices.